Committee Members of Islamic Medical Association of Malaysia (Imam) Symposium 2020 on Covid-19: Planning for the Future - Editor, Chief (International Journal of Human and Health Sciences (IJHHS), 2021)
Abstract not available International Journal of Human and Health Sciences Supplementary Issue: 2021 Page: S1-S2